Improvement of the industrial extraction method of methane homologues - Pedchenko , Mykhailo; Pedchenko , Larysa; Pedchenko, Nazar; Savyk , Vasyl (Academic journal Industrial Machine Building Civil Engineering, 2023)
Absorption processes are one of the main ones in the preparation of hydrocarbon gases. However, in connection with a decrease in the pressure of the input gas, a number of facilities for the preparation of industrial products cannot provide the necessary technological regime and therefore require reconstruction. A typical example is the installation of low-temperature absorption at the main facilities «Solokha» of the gas industry management «Poltavagasvydobuvannya» where there is a decrease in the efficiency of the separation process of natural and oil gases.  According to the results of analytical studies, to eliminate the indicated shortcoming, a variant of the reconstruction of the ULTA MF «Solokha» is proposed, which involves the use of a scheme with preliminary saturation of the regenerated absorbent. This will increase the extraction rate of components by 21.96%.
Keywords: low-temperature absorption; wide fraction of light hydrocarbons; pre-saturation of the absorbent